Distributed Intrusion Detection Systems for Enhancing Security in Mobile Wireless Sensor Networks. (2008) - Mostarda Mostarda, Leonardo Leonardo; Navarra Navarra, Alfredo Alfredo
Abstract : We present an approach to provide Intrusion Detection Systems (IDS) facilities into Wireless Sensors Networks (WSN). WSNs are usually composed of a large number of low power sensors. They require a careful consumption of the available energy in order to prolong the lifetime of the network. From the security point of view, the overhead added to standard protocols must be as light as possible according to the required security level. Starting from the DESERT tool [14, 16, 25] which has been proposed for component-based software architectures, we derive a new framework that permits to dynamically enforce a set of properties of the sensors behavior. This is accomplished by an IDS specification that is automatically translated into few lines of code installed in the sensors. This realizes a distributed system that locally detects violation of the sensors interactions policies and is able to minimize the information sent among sensors in order to discover attacks across the network.